Shortening the Edinburgh postnatal depression scale using optimal test assembly methods: Development of the EPDS‐Dep‐5. (19th January 2021) - Harel, Daphna; Levis, Brooke; Ishihara, Miyabi; Levis, Alexander W.; Vigod, Simone N.; Howard, Louise M.; Thombs, Brett D.; Benedetti, Andrea; ,
Abstract: Aims: This study used a large database to develop a reliable and valid shortened form of the Edinburgh Postnatal Depression Scale (EPDS), a self‐report questionnaire used for depression screening in pregnancy and postpartum, based on objective criteria. Methods: Item responses from the 10‐item EPDS were obtained from 5157 participants (765 major depression cases) from 22 primary screening accuracy studies that compared the EPDS to the Structured Clinical Interview for DSM (SCID). Unidimensionality of the EPDS latent construct was verified using confirmatory factor analysis, and an item response theory model was fit. Optimal test assembly (OTA) methods identified a maximally informative shortened form for each possible scale length between 1 and 9 items. The final shortened form was selected based on pre‐specified validity and reliability criteria and non‐inferiority of screening accuracy of the EPDS as compared to the SCID. Results: A 5‐item short form of the EPDS (EPDS‐Dep‐5) was selected. The EPDS‐Dep‐5 had a Cronbach's alpha of 0.82. Sensitivity and specificity of the EPDS‐Dep‐5 for a cutoff of 4 or greater were 0.83 (95% CI, 0.73, 0.89) and 0.86 (95% CI, 0.80, 0.90) and were statistically non‐inferior to the EPDS. The correlation of total scores with the full EPDS was high ( r = 0.91). Conclusion: The EPDS‐Dep‐5 is a valid short form with minimal loss of information when compared to the full‐length EPDS. The EPDS‐Dep‐5 was developed with OTA methods using objective, pre‐specified criteria, but the approach is data‐driven and exploratory. Thus, there is a need to replicate results of this study in different populations.